The sociology of job training - Bills, David B., 1953- (Amsterdam ; London : JAI, 2003)
How workers learn how to do their jobs is central to an understanding of the changing nature of work in post-industrial society. The role of job or worker training has, however, been underdeveloped in sociological theories of work and the labor market. By most accounts, the ongoing penetration of information technology into the workplace, a transformed socioeconomic lifecourse, managerial preferences for high performance organizations, and the globalization of labour markets have collectively rendered traditional models of skill acquisition badly outmoded. This volume offers sophisticated sociological analyses of job training that go well beyond standard accounts of general versus specific skills and overly simple assumptions about employer and worker behaviour. The chapters examine such topics as the incentives available to employers to provide training, socially structured inequalities in access to training, and cross-societal differences in training institutions. They break new ground in investigating the content of job training as well as its incidence and duration. The contributors to the volume bring to bear both qualitative case study and quantitative research to explore the emerging role of training in post-industrial labor markets.
Fattenin' frogs for snakes? Company investments in job skills training / David Knoke and Song Yang -- Hiring and training in Korean establishments / Wonsup Chang -- Regulating affective labor / Ariel M. Ducey, Heather Gautney and Dominic Wetzel -- What skills to train? an institutional analysis of training consulting organizations / Xiaowei Luo -- Job training as business and community development: reframing theory and practice / Mary Ellen Boyle and Janet Boguslaw -- The connection between training policies and investment in general skills / Laura Cruz-Castro and Gavan Conlon -- Vocational trainikng and the transition to the first job in Germany--new risks at labour market entry? / Dirk Komietzka -- Voluntary put themselves in Harm's way / Kris Paap -- Job training for women leaving welfare: assessing interest in non-traditional employment / Cynthia Negrey .. et al. -- Contextual analyses of company job training / Song Yang -- The effects of age group, technology and social policy on adult women's training participation / Patricia A. Simpson and Linda K. Stroh.
Includes bibliographical references.
Description based on print version record.
Keywords: Occupational training -- Social aspects; Industrial sociology; Employer-supported education -- Social aspects; Sociology: work & labour; Business & Economics -- Labor; Social Science -- Sociology -- General